3x-1+3x+1=90

Simple and best practice solution for 3x-1+3x+1=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-1+3x+1=90 equation:



3x-1+3x+1=90
We move all terms to the left:
3x-1+3x+1-(90)=0
We add all the numbers together, and all the variables
6x-90=0
We move all terms containing x to the left, all other terms to the right
6x=90
x=90/6
x=15

See similar equations:

| (2-m)/6=6 | | -24=-3(5c-7) | | 2-m÷6=6 | | 7a+3a=19 | | 2–m/6=6 | | 9+5(1-6k)=16 | | |x-0.5|+0.3=1 | | b4-3b2-2b+4=0 | | -9b-3+6=28 | | 7(x+4)=7(x-2) | | 16=-3r-4r | | -21-9s=-3(6s+8) | | 2x+6(3)=X(-1)=4 | | 8(5n+9)=25 | | (3y-17)°=(2y+13)° | | -2(c-2)=8 | | 3(5+9v)=35 | | 5k+18=7+3k–3 | | -36=m-22 | | 6.75=0.75x | | -4x+15–x=3–7x–12 | | 2+4a=22 | | 22=18+n | | 8(x+4)–4=4x–1 | | 2x-10=(x+30) | | (2b÷5)-4=((b+3)÷2)-(3÷4) | | -3-12x=153 | | 3.00+0.50x=5.00 | | (n+2)/9+(4n+3)/6=-5+2n | | .1x+4+.1x=5 | | 11x+16=4x+14+72 | | 5/6t=17/8 |

Equations solver categories